Comparative analysis of measurements veracity in heterogeneous and homogeneous airspace complexes - Ignatov, V. O.; Kudrenko, S. O. (Problems of Informatization and Control, 2009)
The method and engineering technique for the comparative analysis of measurements results veracity in heterogeneous and homogeneous airspace complexes are offered. Index parameters of veracity increase at integrating of the information measuring systems are entered. Numerical examples and results of experimental researches of measurements results veracity in heterogeneous and homogeneous complexes are given